Is favoritism a threat to Chinese aid effectiveness?: A subnational analysis of Chinese development projects - Dreher, Axel; Fuchs, Andreas; Hodler, Roland; Parks, Bradley; Raschky, Paul A.; Tierney, Michael J. (CESifo working papers, 2019)
Chinese aid comes with few strings attached, allowing recipient country leaders to use it for domestic political purposes. The vulnerability of Chinese aid to political capture has prompted speculation that it may be economically ineffective, or even harmful. We test these claims by estimating the effect of Chinese aid on subnational economic development - as measured by percapita nighttime light emissions - and whether this effect is different in politically favored jurisdictions than in other parts of the country. Contrary to the conventional wisdom, we do not find that the local receipt of Chinese aid undermines economic development outcomes at either the district level or provincial level. Nor does political favoritism in the allocation of Chinese aid towards the home regions of recipient country leaders reduce its effectiveness. Our results - from 709 provinces and 5,835 districts within 47 African countries from 2001-2012 - demonstrate that Chinese aid improves local development outcomes, regardless of whether such aid is allocated to politically consequential jurisdictions.
Keywords: Graue Literatur